2004
DOI: 10.1110/ps.04911804
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuous protein biotinylation by Escherichia coli biotin protein ligase

Abstract: Biotin protein ligases (BPLs) are enzymes of extraordinary specificity. BirA, the BPL of Escherichia coli biotinylates only a single cellular protein. We report a mutant BirA that attaches biotin to a large number of cellular proteins in vivo and to bovine serum albumin, chloramphenicol acetyltransferase, immunoglobin heavy and light chains, and RNAse A in vitro. The mutant BirA also self biotinylates in vivo and in vitro. The wild type BirA protein is much less active in these reactions. The biotinylation rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
216
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(236 citation statements)
references
References 26 publications
5
216
0
4
Order By: Relevance
“…All of the mutant alleles tested were recessive to the wild-type allele, indicating that they were loss-of-function mutations (6). Subsequent work on several of these mutant strains showed that the defects in biotin utilization reflected compromised ligase activity due to decreased affinities for biotin and/or biotinoyl-adenylate (13,24). We report isolation of the first gain-of-function (genetically dominant) birA superrepressor alleles.…”
Section: Discussionmentioning
confidence: 87%
“…All of the mutant alleles tested were recessive to the wild-type allele, indicating that they were loss-of-function mutations (6). Subsequent work on several of these mutant strains showed that the defects in biotin utilization reflected compromised ligase activity due to decreased affinities for biotin and/or biotinoyl-adenylate (13,24). We report isolation of the first gain-of-function (genetically dominant) birA superrepressor alleles.…”
Section: Discussionmentioning
confidence: 87%
“…However, the determinants of the specificity of BPL-mediated biotinylation are only partially known [132]. One interesting finding was recently made by Choi-Rhee and coworkers [133], who observed less specific biotinylation occurring due to a mutation in the E. coli biotin holoenzyme synthetase/ bio receptor BirA. A mutagenesis of BirA leading to a new sequence specificity could thus be obtained, offering an efficient tool for life science.…”
Section: Conclusion -Views For Future Researchmentioning
confidence: 99%
“…There were no positive signals in the control reactions, confirming the successful removal of holo-AccA1. Even though the in vitro biotinylation of apo-AccA1 by BPL had highest priority, a prolonged incubation resulted in non-specific biotinylation of other proteins as well, most likely due to the promiscuous activity of BPL (Choi-Rhee and Cronan, 2003;Choi-Rhee et al, 2004). Vol.…”
Section: J Microbiolmentioning
confidence: 99%